Taxonomy of Neotropical genera Compsodactylus and Dasyus and notes on claw movement in Macrodactylini (Coleoptera: Scarabaeidae: Melolonthinae) - Fuhrmann, Juares (Zootaxa, 2019)
A taxonomic review of Dasyus LePeletier & Audinet-Serville, 1828 is provided and the classification of Compsodactylus Fuhrmann, 2012 is updated (Coleoptera: Scarabaeidae: Melolonthinae: Macrodactylini). Lectotypes are designated for the following names: Dasyus collaris luridipennis Moser, 1918, Dasyus variabilis Moser, 1918 and Isonychus argentinus Moser, 1919. Compsodactylus argentinus (Moser, 1919) is a new combination to the species formerly placed in Isonychus Mannerheim, 1829. The following four synonymies are proposed: C. scabrosus Fuhrmann, 2012 is a new synonym of C. argentinus; Dasyus fulvipennis Blanchard, 1850 and Dicrania hirsuta Frey, 1970 are both new synonyms of Dasyus collaris LePeletier & Audinet-Serville, 1828; and Calodactylus pilicollis Frey, 1974 is a new synonym of D. variabilis. Two synonymies formerly proposed but sometimes omitted are here confirmed: D. nigellus Blanchard, 1850 and D. collaris luridipennis synonymies of D. collaris. The male of Compsodactylus parvulus (Frey, 1970) is described for the first time. Diagnoses, keys, distributional data, and a discussion about macrodactyline tarsal claws are included.